Sedimentation and sediment core profile of heavy metals in the Owabi reservoir in Ghana. Issue 2 (1st July 2019) - Nartey, Nora N.; Hogarh, Jonathan N.; Antwi‐Agyei, Philip; Nukpezah, Daniel; Abaidoo, Robert C.; Obiri‐Danso, Kwasi
Abstract: Tropical reservoirs are important for numerous socioeconomic and ecological reasons, including water supply, fishing and flood control. These functions are easily compromised, however, when reservoirs undergo accelerated sedimentation with increased inputs of chemical contaminants. The present study applied the concept of sediment core analysis to evaluate the sedimentation rate in Owabi Reservoir, which has served as a source of drinking water supply in Kumasi, Ghana, for nearly a century. The temporal variation of contamination from heavy metals was also assessed over this period. The sedimentation rate for Owabi Reservoir was estimated to be 6.82 mm/year, suggesting a relatively low rate of sedimentation, which is ecologically healthy in preventing a rapid loss of reservoir water volume. Heavy metal concentrations in the sediment cores taken from the reservoir reflected varying degree of contamination from the 1930s to 2010s. The concentration of iron (Fe) (1, 560–1, 770 mg/kg) was found to be the highest among the metals in the sediment core, while mercury (Hg) concentration (0.01–0.04 mg/kg) was the lowest. Lead (Pb) contamination peaked in the 1980s. Arsenic (As) and mercury (Hg) contamination exhibited more recent peaks in the 2000s, coinciding with recent widespread issues of artisanal and small‐scale gold mining (ASGM) in Ghana. Thus, even though ASGM activities are known to occur in remote districts, releases from such activities might eventually contaminate reservoirs designated as urban drinking water supplies.